Pay Gap Between Male And Female Physicians - Weeks, Bill; Ventelou, Bruno (Health Affairs, 2020)
Using New York State survey data for 1999–2017, Anthony Lo Sasso and coauthors (Feb 2020) found sex-based disparities in physicians’ starting pay, even after they adjusted for important variables. We have two comments on the research. First, when there are substantial differences in the sample’s high-paying specialty distribution between the sexes, cross-specialty comparisons may conflate specialty choice with sex-based disparities within a specialty.